Performance Analysis of Time Difference of Arrival and Angle of Arrival Estimation Methods for GSM Mobile Phone Localization - Zimmermann, Lars; Götz, Alexander; Fischer, Georg; Weigel, Robert (Communication, Signal Processing & Information Technology, 2017)
The localization methods time difference of arrival (TDOA) and angle of arrival (AOA) are investigated in their capability of high-resolution detection of GSM signals. Because GSM is of narrowband nature, a bandwidth expansion technique that significantly increases the resolution of TDOA is introduced. The algorithms maximum likelihood estimator (for TDOA), root multiple signal classification and estimation of signal parameters via rotational invariance techniques (for AOA) are proposed as a reference for each method. Simulations conducted with noisy signals and multipath propagation demonstrate the potential of TDOA for GSM localization, especially for search and rescue applications. AOA on the other hand is very sensitive to multipath, and is therefore only recommended for open space scenario
Keywords: Time difference of arrival estimation; Direction of arrival estimation; GSM; Maximum likelihood estimation; Multiple signal classification; Estimation of signal parameters via rotational invariance techniques